Pengembangan Sistem Business Intelligence untuk Analisa Pola Tindak Pidana di Pengadilan Negeri Pekanbaru - dea pricillia mulyani; ardianto wibowo; Dini Hidayatul Qudsi (Jurnal Komputer Terapan, 2018)
The District Court is an agency that handles criminal offenses in Pekanbaru. Based on the results of an interview with the Registrar's Office of Law, it is known that the Pekanbaru District Court reported and analyzed cases regarding the criminal acts of the Police and Prosecuting Office, where it was required to report criminal acts. Therefore, a website-based Business Intelligence (BI) system is built to process criminal data that is visualized into dashboards to support the Legal Registrar in obtaining criminal patterns that occur in Pekanbaru, and allows evaluating the internal performance of the Pekanbaru District Court, using the CI framework and use the PHP programming language. Based on UAT testing the function on the system has been successfully built and running well, usability testing results with a questionnaire to the Registrar's Office of Law, showing that the system is 94% easy to use, 91% studied, 95% useful, and 88% satisfying. And system efficiency found that the measurement of performance levels on web pages based on certain aspects get a percentage of 67% and the time needed to load a web page is a percentage of 70%.